Cervical screening uptake and its predictors among rural women in Malaysia - Gan, D.E.H.; Dahlui, M. (2013)
INTRODUCTION: Cervical cancer is the third most common cancer among Malaysian women. However, the uptake of cervical cancer screening--Pap smear--by women in Malaysia has been low and remains a challenge. This study was conducted to assess the cervical screening practices of rural women in Malaysia and to examine the factors associated with such practices. METHODS: A cross-sectional survey was conducted in five rural districts in Perak, Malaysia. 1,000 households were selected through multistage random sampling. Women aged 20-64 years were interviewed by trained enumerators using structured questionnaires. Binomial logistic regression was used to identify predictors of cervical screening through univariate and multivariate analyses. RESULTS: Among the 959 respondents, only 48.9 had undergone Pap smear at least once in the past three years. Women in the age group 40-49 years (odds ratio 3.027, 95 confidence interval 1.546-5.925; p < 0.005) were found to be significantly more likely to attend cervical cancer screening as compared to those in the age group 20-29 years. Other significant predictors were being married with children, having knowledge of cervical cancer symptoms, receiving relevant information regarding cervical cancer from health personnel or campaigns, being engaged in family planning and receiving encouragement from husbands. CONCLUSION: Efforts to boost the uptake of Pap smear screening among the rural population should be targeted toward the predictors of positive uptake.